Association between the dietary index for gut microbiota and frailty: the mediating role of body mass index - Lei, Jiawei; Feng, Tingting; Tian, Tian; Zhuang, Ziyun; Zhang, Guilei; Liu, Ying; Yang, Zhenrong; Wang, Yuting; Zhang, Xin; Sun, Wei; Wang, Jiahe (Frontiers in Nutrition, 2025)
BackgroundThe Dietary Index for Gut Microbiota (DI-GM), a newly introduced metric, indicates gut microbiota diversity. However, its correlation with frailty remains unexplored.MethodA total of 25,320 individuals were included in the 2007–2020 National Health and Nutrition Examination Survey (NHANES). Dietary recall data were calculated by averaging intake values from two separate 24-h dietary recall interviews. Frailty was assessed using the 49-item frailty index. The relationship between DI-GM and the frailty phenomenon was examined by applying a weighted logistic regression model. A comprehensive sensitivity analysis was undertaken, incorporating restricted cubic splines for modeling non-linear effects, stratified subgroup analyses to explore effect modification, and multiple imputation techniques to address potential missing data concerns.ResultsHigher DI-GM scores and gut microbiota-beneficial dietary components were significantly associated with reduced prevalence of frailty (Frailty Index: OR = 0.987, 95% CI: 0.977–0.997, P = 0.014; Frailty: OR = 0.941, 95% CI: 0.902–0.980, P = 0.004). Restricted cubic spline analysis revealed a non-linear relationship between DI-GM and frailty. Body Mass Index (BMI) mediated this relationship, accounting for 17.57% of the association.ConclusionWe concluded that a higher DI-GM score is associated with a lower risk of frailty, partly via BMI mediation. Future research should validate these findings using longitudinal studies.